Continuous chemical operations and modifications on magnetic γ-Fe2O3 nanoparticles confined in nanoliter droplets for the assembly of fluorescent and magnetic SiO2@γ-Fe2O3. Issue 95 (5th October 2015) - Ferraro, D.; Lin, Y.; Teste, B.; Talbot, D.; Malaquin, L.; Descroix, S.; Abou-Hassan, A.
Abstract : An automated droplet microfluidic platform is described for the manipulation of magnetic nanoparticles and their assembly with fluorescent silica nanoparticles. Abstract : We present a microfluidic platform that allows undergoing different chemical operations in a nanoliter droplet starting from the colloidal suspension of magnetic iron oxide (γ-Fe2 O3 ) nanoparticles "NPs" (ferrofluid). These operations include: mixing, flocculation, magnetic decantation, colloidal redispersion, washing, surface functionalization, heating and colloidal assembly. To prove the platform capabilities, we produced fluorescent and magnetic nanoassemblies composed of fluorescent silica and magnetic NPs.